Associations between Plasma Choline Metabolites and Genetic Polymorphisms in One-Carbon Metabolism in Postmenopausal Women: The Women's Health Initiative Observational Study. Issue 11 (16th September 2020) - Ilozumba, Mmadili N; Cheng, Ting-Yuan D; Neuhouser, Marian L; Miller, Joshua W; Beresford, Shirley A A; Duggan, David J; Toriola, Adetunji T; Song, Xiaoling; Zheng, Yingye; Bailey, Lynn B; Shadyab, Aladdin H; Liu, Simin; et al.
ABSTRACT: Background: Choline plays an integral role in one-carbon metabolism in the body, but it is unclear whether genetic polymorphisms are associated with variations in plasma choline and its metabolites. Objectives: This study aimed to evaluate the association of genetic variants in choline and one-carbon metabolism with plasma choline and its metabolites. Methods: We analyzed data from 1423 postmenopausal women in a case-control study nested within the Women's Health Initiative Observational Study. Plasma concentrations of choline, betaine, dimethylglycine (DMG), and trimethylamine N-oxide were determined in 12-h fasting blood samples collected at baseline (1993–1998). Candidate and tagging single-nucleotide polymorphisms (SNPs) were genotyped in betaine-homocysteine S-methyltransferase ( BHMT ), BHMT2, 5, 10-methylenetetrahydrofolate reductase ( MTHFR ), methylenetetrahydrofolate dehydrogenase (NADP+ dependent 1) ( MTHFD1 ), 5-methyltetrahydrofolate-homocysteine methyltransferase ( MTR ), and 5-methyltetrahydrofolate-homocysteine methyltransferase reductase ( MTRR ). Linear regression was used to derive percentage difference in plasma concentrations per variant allele, adjusting for confounders, including B-vitamin biomarkers. Potential effect modification by plasma vitamin B-12, vitamin B-6, and folate concentrations and folic-acid fortification periods was examined. Results: The candidate SNP BHMT R239Q (rs3733890) was associated with lower concentrations of plasma betaine and DMG concentrations (−4.00% and −6.75% per variant allele, respectively; both nominal P  < 0.05). Another candidate SNP, BHMT2 rs626105 A>G, was associated with higher plasma DMG concentration (13.0%; P < 0.0001). Several tagSNPs in these 2 genes were associated with plasma concentrations after correction for multiple comparisons. Vitamin B-12 status was a significant effect modifier of the association between the genetic variant BHMT2 rs626105 A>G and plasma DMG concentration. Conclusions: Genetic variations in metabolic enzymes were associated with plasma concentrations of choline and its metabolites. Our findings contribute to the knowledge on the variation in blood nutrient concentrations in postmenopausal women.